An examination of the Korean community in the Dominican Republic - NELSON ORTEGA (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: This study aims to introduce and characterize Koreans residing in the Dominican Republic and record salient features of their daily lives.Methodology: This paper uses a combination of quantitative and qualitative data, including surveys completed by 108 adults of Korean ancestry, interviews with prominent members of the Korean community, and first-hand observation, to chronicle the lives and economic activities of Koreans in the Dominican Republic.Findings: According to the survey findings, Koreans in the Dominican Republic interact primarily through their churches and families. Although acculturation appears to be taking place among the young who have shown an interest in Dominican cuisine, dance, and music, the average Korean spends little time interacting with people outside their immediate social circles. Crime, government corruption, and cultural differences between Korean employers and Dominican workers are the most pressing issues for Koreans in the Dominican Republic.Novelty/Implications: Despite their contributions, little is known about how Koreans living in the Dominican Republic adapt to their new environment, how they go about their daily lives, and what challenges they face. The community of roughly 700 Koreans living in the Dominican Republic is being studied for the first time in this paper.